Przydatność narzędzi rachunkowości zarządczej w zarządzaniu strategicznym - Dyduch, Alina; Bek-Gaik, Bogusława (Usefulness of the management accounting tools in strategic management, 2006)
Nowadays there are two variants of management accounting: traditional operating accounting and strategic management accounting. It should be emphasized that strategic accounting has developed in recent years as a response to the growing demand among enterprises for information that would support the building and implementation of operating strategy. This article discusses selected strategic management accounting tools and their usefulness in management of contemporary enterprises. Particular attention has been paid to capital budgeting procedure, balanced scorecard and economic value added.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 97-104